2020
DOI: 10.31234/osf.io/jyuvz
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Situating Space: Using a Discipline-Focused Lens to Examine Spatial Thinking Skills

Abstract: Spatial skills are an important component of success in STEM fields. A majority of what we know about spatial skills today is a result of over 100 years of research focused on understanding and identifying the kinds of skills that make up this skill set. Over the last two decades, the field has recognized that unlike the spatial skills measured by psychometric tests developed by psychology researchers, the spatial problems faced by STEM experts vary widely and are multifaceted. Thus, many psychological researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
(132 reference statements)
0
1
0
Order By: Relevance
“…Spatial ability relevant to computer programming (Jones & Burnett, 2008) includes visualizing processes and data flows (Cheah, 2020), while surgery and geology require visualizing cross sections of anatomical structures and geological sites, respectively (Kali & Orion, 1996; Orion et al, 1997; Rochford, 1985). There are abundant examples illustrating how STEM education requires students to engage in such different types or categories of spatial thinking as mental rotation, perspective taking, and navigation (Atit et al, 2020; Cheng, 2017), and substantial research has indicated that spatial skills predict outcomes not only in education but also in careers (Buckley et al, 2018; Wai et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Spatial ability relevant to computer programming (Jones & Burnett, 2008) includes visualizing processes and data flows (Cheah, 2020), while surgery and geology require visualizing cross sections of anatomical structures and geological sites, respectively (Kali & Orion, 1996; Orion et al, 1997; Rochford, 1985). There are abundant examples illustrating how STEM education requires students to engage in such different types or categories of spatial thinking as mental rotation, perspective taking, and navigation (Atit et al, 2020; Cheng, 2017), and substantial research has indicated that spatial skills predict outcomes not only in education but also in careers (Buckley et al, 2018; Wai et al, 2009).…”
Section: Introductionmentioning
confidence: 99%